Tingkat Kepuasan Pasien Diabetes Mellitus Tipe 2 Terhadap Pelayanan Tenaga Kefarmasian Di Puskesmas Moncongloe Kabupaten Maros - Andi Dian Fitri Amoer; Frederika Tangdilintin; Anshar Saud; Muh. Akbar Bahar (Jurusan Farmasi Poltekkes kemenkes Makassar, 2025)
ABSTRACT Diabetes mellitus (DM) is one of the serious health problems and the biggest cause of death in the world. One of the districts that has the largest number of people with diabetes mellitus in South Sulawesi Province is Maros Regency. Pharmacists play a very important role in the therapeutic process of DM patients to improve the quality of life of patients. Objective. This study aims to determine the level of patient satisfaction based on perceptions of pharmaceutical services at the Moncongloe Health Center, Maros Regency. Methods. This study is a quantitative study with cross sectional method. This research instrument is a questionnaire adopted from previous studies that have been proven valid and reliable. This research was conducted at the Moncongloe Health Center, Maros Regency, South Sulawesi Province in January 2024. Results. This study shows that respondents gave a satisfied perception of the overall service of pharmaceutical personnel with a total percentage of 86%. In the aspect of prescription screening, the dominant patient was satisfied with a percentage of 43%; the aspect of drug preparation 66%; the aspect of drug information communication and education 46.6%; drug monitoring 42.8% of each patient was satisfied. Conclusion. The overall level of patient satisfaction with the perception of pharmaceutical personnel services at the Moncongloe Health Center, Maros Regency is 86% which is included in the satisfied category.